2011
DOI: 10.1093/abbs/gmr034
|View full text |Cite
|
Sign up to set email alerts
|

<italic>In vivo</italic> study on the histocompatibility and degradation behavior of biodegradable poly(trimethylene carbonate-co-d,l-lactide)

Abstract: The aim of this study was to explore the in vivo behavior and histocompatibility of poly(trimethylene carbonateco-D,L-lactide) (PDLLA/TMC) and its feasibility of manufacturing cardiovascular stents. Copolymers with 50/50 molar ratio were synthesized by ring-opening polymerization with TMC and D, L-LA, or TMC and L-LA. Poly (L-lactide) (PLLA) was synthesized as a control. The films of the three polymers were implanted into 144 Wistar rats. At different time points of implantation, polymer films were explanted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Other than the ‘bulk degradation mode’ of PDLLA, PTMC has been shown to degrade by surface erosion approach [ 18 , 19 ], avoiding the sharp attenuation of mechanical strength during fragmentation of the matrix. In addition, PDLLA cleaves by hydrolysis into acidulous lactic acid [ 20 , 21 ], which has an adverse effect on surrounding tissue. It has been demonstrated that enzymes and reactive oxygen species secreted by phagocytic cells play an important role in the in vivo degradation of PTMC [ 22 , 23 ], and it degrades without the formation of acidic compounds, which is an advantage as regenerative material.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the ‘bulk degradation mode’ of PDLLA, PTMC has been shown to degrade by surface erosion approach [ 18 , 19 ], avoiding the sharp attenuation of mechanical strength during fragmentation of the matrix. In addition, PDLLA cleaves by hydrolysis into acidulous lactic acid [ 20 , 21 ], which has an adverse effect on surrounding tissue. It has been demonstrated that enzymes and reactive oxygen species secreted by phagocytic cells play an important role in the in vivo degradation of PTMC [ 22 , 23 ], and it degrades without the formation of acidic compounds, which is an advantage as regenerative material.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond 60 days, the molecular weight of PDLLA-TMC decreased below 10,000 kDa, in agreement with the rapid mass loss observed in this period. [7] In our study, the weight average molecular weight (Mw) decreased from 151,000 to 10,000 Da.…”
Section: [6]mentioning
confidence: 48%
“…Guo et al, [7] in an experiment using 144 Wistar rats, stated that the molecular weight of PLLA decreased rapidly, from 72,000 to 68,000 kDa in the first 2 days and to 32,000 kDa 15 days later. Similar molecular weight decreases were obtained for PLLA-TMC and PDLLA-TMC copolymers, although PLLA-TMC appeared more resistant to hydrolytic degradation.…”
Section: [6]mentioning
confidence: 99%
“…One of the few studies in which immunological parameters were evaluated was performed in vivo and PLTMC/PLLA were implanted subcutaneously (GUO et al 2011). Fewer immune cells infiltrated tissues around PLTMC than in the PLLA implanted rats (GUO et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One of the few studies in which immunological parameters were evaluated was performed in vivo and PLTMC/PLLA were implanted subcutaneously (GUO et al 2011). Fewer immune cells infiltrated tissues around PLTMC than in the PLLA implanted rats (GUO et al 2011). However, some macrophage infiltration was observed in a study in which the polymers were implanted into rat peritoneal cavity (DARGAVILLE et al 2011).…”
Section: Discussionmentioning
confidence: 99%